Innovations in Spinal Deformities and Postural Disorders - Josette Bettany-Saltikov; Sanja Schreiber (IntechOpen, 2017)
Innovations in Spinal Deformities and Postural Disorders presents a compendium of innovative work in the management of spinal deformities and postural disorders. The chapters were carefully selected with clinicians, researchers, patients and parents in mind. All of these stakeholders are important links in the management of spinal deformities and disorders. It is our hope that all will remain open to new ideas in the field and will be able to evaluate the material carefully and in ways that are objective and evidence based. We hope that the different chapters in the book will stimulate readers to be original and innovative in their own centers in order to help our patients in the best way possible. This book contains new information on the 3D measurement of, as well as new approaches to, the 3D conservative, including exercises and braces, and surgical treatments for patients with spinal deformities and postural disorders.
English
Keywords: Medicine; Surgery; Orthopedics; Health Sciences